The Opportunities of Introducing Oral History into the Curriculum of Andragogy Studies (Training and Practice : Journal of Educational Sciences, 2007)
The study - based on examples from Mircea Eliade - proposes to ease the traditional juxtaposition of historiology and collective memory, a term used for oral history by Jan Assman. This concept of collective memory is employed as a method by András Németh and Éva Szabolcs as well as a „pedagogical memory” to attain a steady factor in the educational processes. The study, focusing on the education of history and then on the history of andragogy, follows the suggestions of Ruth Tudor and Bob Stradling, both of whom propose the use of oral history in curriculum studies. The author admits that the Hungarian approach to the education of history is rather cautious about methodological innovations. Yet, as the study argues, more and more oral history resources are available in Hungary, collections which may supply ample material for educational purposes. One example given is the Oral History Archives of the 1956 Institute, Budapest. The author proposes, that - within the education of the history of andragogy - the knowledge and expertise lying within the oral history resources on adult educational courses as folk high schools, reading circles and free universities may represent a highly valuable asset. One of the proposed examples is the history of the National Association of People’s Colleges (NÉKOSZ), not only richly documented through personal memoirs (e.g. that of Ferenc Pataki), but made available on various film as well. The author states that these and similar materials may serve good grounds as methodological tools both for seminary discussions and for individual research on the history of andragogy.